Development of Inquiry-based E-LKPD on Plant Growth and Development to Train Critical Thinking Skills - Khofifah, Alfina Siti; Rinie Puspitawati; Indah, Novita Kartika (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2025)
Abstract The development of inquiry-based E-LKPD was developed to fulfil the demands of education in mastering technology and 4C skills. This research has successfully developed inquiry-based E-LKPD to train students' critical thinking skills that are valid, practical, and effective. The methods used were validation sheet, response questionnaire, and test sheet. The validity of the E-LKPD was assessed by two validators, namely media expert lecturers and material expert lecturers. The practicality of E-LKPD was measured based on the observation data of the implementation of learning activities, while effectiveness is measured through data on learning outcomes of XII grade students obtained from the E-LKPD final assessment test and the achievement of critical thinking indicators.The trial phase was conducted on 20 students of class XII MIPA at SMA Ta'miriyah Surabaya. Based on the results of the study, it shows that the E-LKPD developed is very valid with a validity score from both validators of 97.33%, the practicality of E-LKPD is declared very practical with the observation score of the implementation of learning activities reaching 97.15% and student responses reaching 97.6%, the effectiveness of E-LKPD is declared very effective with the percentage of completeness of the E-LKPD final assessment reaching 100%. Thus the E-LKPD is declared feasible to be implemented in students. Keywords: E-LKPD, critical thinking, inquiry.